Analysis of the Effect of Investment, Unemployment Rates, Population on In Economic Growth in West Java - Tesa Sindy Prameswari Putri; Zainal Arifin; Muhammad Firmansyah (Yayasan Riset dan Pengembangan Intelektual, 2024)
Economic growth is an important issue that needs attention from the government and stakeholders. The objective of this study is to analyze the influence of foreign investment, domestic investment, open unemployment rate, and population on economic growth in West Java. The methodology in this research is panel data regression. The findings of this research indicate that FDI have a positive and not significant effect, Domestic Investment and Population have a significant positive effect, and the Open Unemployment Rate has a significant negative effect on economic growth in West Java. The government can continue to improve regulations and bureaucracy, especially in terms of investment so that investors have an interest in investing in West Java.